Binary and quaternary mixtures of perfluoroalkyl substances (PFAS) differentially affect the immune response to influenza A virus infection - Christina M. Post; Carrie McDonough; B. Paige Lawrence (Journal of Immunotoxicology)
Per- and polyfluoroalkyl substances (PFAS) are anthropogenic organofluorine compounds that persist indefinitely in the environment and bioaccumulate throughout all trophic levels. Biomonitoring efforts have detected multiple PFAS in the serum of most people. Immune suppression has been among the most consistent effects of exposure to PFAS. PFAS often co-occur as mixtures in the environment, however, few studies have examined immunosuppression of PFAS mixtures or determined whether PFAS exposure affects immune function in the context of infection. In this study, mixtures containing two or four different PFAS and a mouse model of infection with influenza A virus (IAV) were used to assess immunotoxicity of PFAS mixtures. PFAS were administered via the drinking water as either a binary mixture of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) or quaternary mixture of PFOS, PFOA, perfluorohexane sulfonate (PFHxS), and perfluorononanoic acid (PFNA). The results indicated that the binary mixture affected the T-cell response, while the quaternary mixture affected the B-cell response to infection. These findings indicate that the immunomodulatory effects of PFAS mixtures are not simply additive, and that the sensitivity of immune responses to PFAS varies by cell type and mixture. The study also demonstrates the importance of studying adverse health effects of PFAS mixtures.